Status of the quality of education and accountability unit in the educational process from the point of view of the principals of Kasbah Al Mafraq schools - Alshdefat, Muneera Abdalkareem (Journal of Educational and Psychological Sciences, 2020)
This Present study aimed at finding out the Status of the quality of education and accountability unit in the educational process from the point of view of the principals of Kasbah Al Mafraq schools To achieve the goal of the study, a descriptive development methodology was developed, which was developed in three areas (evaluation criteria, cooperation and coordination, feedback and incentives) (21) items, and verified their validity and stability, and then distributed to the sample of the study consisting of (167) managers and directors in schools Kasbah Mafraq. The study results showed that the degree of appreciation and the reality of Status of the quality of education and accountability unit in the educational process from the point of view of the principals of Kasbah Al Mafraq schools was at low degree The average of the tool as a whole was (2.00) with a standard deviation of (.55) and at the level of domains, All of them were rated low, with feedback and incentives having the highest average (2.09) followed by evaluation criteria (2.00) and cooperation and coordination (1.90), and the results showed that there were no statistically significant differences in The study sample of the Status of the quality of education and accountability unit in the educational process from the point of view of the principals of Kasbah Al Mafraq schools, according to gender, at the macro level of the instrument and on all dimensions. The study recommended in light of those results the necessity for that efforts should be join efforts to support and deepen the concept of quality of education and accountability, cooperation and coordination between the quality unit of education and accountability and educational leaders, and try to provide incentives and thanks to those who deserve it, to achieve the concept of guidance and support.